Colposcopic evaluation in cases of persistent inflammatory Pap smear - Choudhary, Paridhi; Tyagi, Mamta; Gupta, Smriti; Gupta, Manvi; Pandey, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The aim of the study was to assess the colposcopic evaluation in cases of persistant inflammatory Papanicolaou (Pap) smear. Methods: This was a prospective analytical study, conducted amongst 78 women attending the outpatient department of obstetrics and gynaecology at Subharti Medical College. Pap smear was performed by the conventional method and colposcopy was done for all 78 sexually active women who came with complaints of pain abdomen, irregular cycles, white discharge per vaginum and urinary tract infections. Final correlation of Pap smear and colposcopy were based on histopathology and human papillomavirus deoxyribonucleic acid (HPV DNA). Results: In this study of 78 women, 21% of women had normal colposcopic findings whereas 79% had abnormal colposcopic findings. Histopathological examination (HPE) findings revealed that 69% women had cervical intraepithelial neoplasia (CIN) 1, 23% had CIN II, 6% had CIN III and 3% had SCC. 25% women tested positive for HPV DNA and 75% women tested negative for HPV DNA. Conclusions: Patients with persistent inflammatory Pap smear despite undergoing treatment show changes on Colposcopic directed biopsies.